Definition of optimal agricultural plastic waste collection centers with advanced spatial analysis tools - Phoebe-Zoe Morsink-Georgali (Elsevier, 2021)
The volumes of agricultural plastic waste (APW) generated are continuously rising, creating the need for sustainable management, especially in countries with large agricultural areas. This paper proposes a location allocation model for the establishment of centers for process and recycling of APW, presenting an enormous opportunity for the plastics manufacturing industry. The proposed model was tested with data retrieved for the case of Cyprus, an island EU member state well renowned for its agricultural production. Under this context, the greenhouses in Cyprus were categorized in clusters based on their geographical dispersion and mapped with the use of geographical information system (GIS). The GIS tool also enabled the calculation of the annual APW generation. An optimized design of the APW supply chain, which achieves the lowest energy needs, was delivered. Non-Linear Programming was employed to indicate the optimal locations for the establishment of collection points within each cluster and province of the island as well as the theoretical optimal geographic location for the establishment of an APW recycling plant in the island state. Based on the location-allocation analysis findings, design specifications for the APW recycling units are also proposed.